Suppression of Water Absorption by Molecular Design of Ionic Liquid Electrolyte for Li–Air Battery. Issue 3 (27th October 2016) - Thomas, Morgan L.; Oda, Yoshiki; Tatara, Ryoichi; Kwon, Hoi‐Min; Ueno, Kazuhide; Dokko, Kaoru; Watanabe, Masayoshi
Abstract : In this study, the effect of water on the oxygen reduction reaction is initially investigated in aprotic ionic liquids by cyclic voltammetry, revealing that the presence of water significantly deteriorates the reversibility of the oxygen reduction reaction and oxygen evolution reaction, which will be detrimental to performance of a practical lithium–air battery. In order to prevent moisture intrusion from ambient air, a hydrophobic electrolyte is then designed and the moisture content in the electrolyte exposed to ambient air is greatly suppressed, to less than 1 wt% at 30 °C and 90% RH (relative humidity). Charge and discharge tests using the hydrophobic electrolyte are reversible for several cycles even in O2 with a RH of 28%. This approach for enhancing the hydrophobicity of the electrolyte, and thus the inherent equilibrium moisture content, for the Li–air battery demonstrates the possibility for improved stability to ambient moisture. Abstract : Dramatic reduction of inherent equilibrium water content for a solvate ionic liquid is achieved by judicious choice of mixture components to enable open operation of a lithium–air battery in humid conditions. The designed electrolyte exhibits improved stability for reversibility of oxygen reduction reaction/oxygen evolution reaction and improved performance under galvanostatic cycling despite the presence of moisture.